Situation Report: Romania, 7 July 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Implementing the Five-Year Plan Ahead of Schedule New Metallurgical Combine to Be Built at Calarasi New Educational Measures Foreign Contacts of Orthodox Church Leaders Gabonese President in Romania Discussions on Planned European CP Conference Continue Youth Exchanges with US and Britain West Germany's Free Democratic Party Sends Delegation to Romania Training Party, TU, and Economic Specialists from Developing Countries Israeli CP Delegation Visits Romania